Protein markers of cancer-associated fibroblasts and tumor-initiating cells reveal subpopulations in freshly isolated ovarian cancer ascites - Wintzell, My (BioMed Central, 2012)
BACKGROUND: In ovarian cancer, massive intraperitoneal dissemination is due to exfoliated tumor cells in ascites. Tumor-initiating cells (TICs or cancer stem cells) and cells showing epithelial-mesenchymal-transition (EMT) are particularly implicated. Spontaneous spherical cell aggregates are sometimes observed, but although similar to those formed by TICs in vitro, their significance is unclear. METHODS: Cells freshly isolated from malignant ascites were separated into sphere samples (S-type samples, n=9) and monolayer-forming single-cell suspensions (M-type, n=18). Using western blot, these were then compared for expression of protein markers of EMT, TIC, and of cancer-associated fibroblasts (CAFs). RESULTS: S-type cells differed significantly from M-type by expressing high levels of E-cadherin and no or little vimentin, integrin-β3 or stem cell transcription factor Oct-4A. By contrast, M-type samples were enriched for CD44, Oct-4A and for CAF markers. Independently of M- and S-type, there was a strong correlation between TIC markers Nanog and EpCAM. The CAF marker α-SMA correlated with clinical stage IV. This is the first report on CAF markers in malignant ascites and on SUMOylation of Oct-4A in ovarian cancer. CONCLUSIONS: In addition to demonstrating potentially high levels of TICs in ascites, the results suggest that the S-type population is the less tumorigenic one. Nanog(high)/EpCAM(high) samples represent a TIC subset which may be either M- or S-type, and which is separate from the CD44(high)/Oct-4A(high) subset observed only in M-type samples. This demonstrates a heterogeneity in TIC populations in vivo which has practical implications for TIC isolation based on cell sorting. The biological heterogeneity will need to be addressed in future therapeutical strategies.